2020
DOI: 10.3892/ol.2020.11568
|View full text |Cite
|
Sign up to set email alerts
|

Ubiquitin‑specific peptidase 17 promotes cisplatin resistance via PI3K/AKT activation in non‑small cell lung cancer

Abstract: The suppression of ubiquitin-specific peptidase 17 (USP17) has previously been found to result in reduced tumorigenesis and invasion of non-small cell lung cancer (NSCLC) cells. However, the functions and underlying mechanisms of USP17 in NSCLC progression remain unclear. In the present study, cisplatin treatment was found to upregulate USP17 expression in a dose-dependent manner. Furthermore, USP17-overexpressing (USP17-OE) NSCLC A549 and H1299 cells were generated for mechanistic studies. The results from th… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
4
0

Year Published

2021
2021
2022
2022

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(4 citation statements)
references
References 44 publications
0
4
0
Order By: Relevance
“…The PI3K/AKT pathway is related to the development and progression of a range of cancers [ 38 40 ]. Zhang et al [ 41 ] discovered that PI3K/AKT is involved in cisplatin resistance in NSCLC. Zhang et al [ 42 ] showed that PI3K/Akt signaling pathway inhibition enhanced AZD9291-induced cell death.…”
Section: Discussionmentioning
confidence: 99%
“…The PI3K/AKT pathway is related to the development and progression of a range of cancers [ 38 40 ]. Zhang et al [ 41 ] discovered that PI3K/AKT is involved in cisplatin resistance in NSCLC. Zhang et al [ 42 ] showed that PI3K/Akt signaling pathway inhibition enhanced AZD9291-induced cell death.…”
Section: Discussionmentioning
confidence: 99%
“…USP17 subfamily genes encoding deubiquitinating enzymes were identified as immediate early genes that can be rapidly induced in response to cytokine stimulation in mice and humans [ 31 ]. Specifically, USP17 has been shown to regulate inflammation, cell motility, Th17 cell development, and oncogenesis [ 32 ]. Moreover, high levels of USP17 have been shown to promote G1-S transition and cell proliferation in multiple cancer cell types.…”
Section: Discussionmentioning
confidence: 99%
“…It has been reported that CDDP increased the levels of USP17 expression. USP17 also induced the NSCLC cell proliferation through PI3K/AKT activation [44]. HSPA12B belongs to the HSP70 protein family that is directly associated with CDDP resistance through p-IκBα and p-AKT upregulations and caspase-3 downregulation in lung tumor cells [45].…”
Section: Lung Cancermentioning
confidence: 99%